TINDAK PIDANA PENCURIAN YANG DILAKUKAN PADA SAAT BENCANA ALAM DITINJAU DARI SUDUT KRIMINOLOGI (STUDI KASUS DI POLISI SEKTOR RUMBAI) - Virsa Ferasar; Syaifullah Yophi; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
From the results of research and discussion, it can be concluded that the First, the factors that caused the criminal act at the time of natural disasters in the jurisdiction of the Police Sector Tassel is because of the intention of the perpetrators of the crime of theft , home because of the opportunities left by the owner to evacuate and need urgent with the slow pace of assistance from the government the pretext that got refuge , Second , efforts are being made to prevent the occurrence of the crime of theft during a natural disaster is to do preventive measures , curative as well as to provide guidance to the public. While the authors suggested, the first in tackling and minimizing the crime of theft committed during natural disasters must involve all stakeholders, ranging from government, police agencies even relevant in meeting the needs of security and comfort for refugees in the camps. Second, Related to the efforts made in order to prevent the crime of theft at the time of natural disasters should be done in a sustainable and continuous, it aims to create and provide education to the community on the importance of adhering to the norms and obey the law in order to prevent the occurrence of a crime, particularly the crime of theft at the time of natural disasters.Keywords : Crime - Theft - When Natural Disasters – Criminology